1997
DOI: 10.1097/00004647-199704000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Improved Perfusion with rt-PA and Hirulog in a Rabbit Model of Embolic Stroke

Abstract: We conducted a study using diffusion-weighted (DWI) and perfusion-weighted (PWI) magnetic resonance imaging (MRI) to evaluate the efficacy of thrombolysis in an embolic stroke model with recombinant tissue plasminogen activator (rt-PA) and hirulog, a novel direct-acting antithrombin. DWI can identify areas of ischemia minutes from stroke onset, while PWI identifies regions of impaired blood flow. Right internal carotid arteries of 36 rabbits were embolized using aged heterologous thrombi. Baseline DWI and PWI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Sections were photographed and inspected for gross hemorrhage. Five brain sections were visually inspected for gross hemorrhage and scored by a rater blinded to treatment using methods previously published by our group (Yenari et al, 1997a(Yenari et al, , 1997b(Yenari et al, , 2006. Only cerebral hemorrhages visible to the naked eye were scored: 0, if there was no gross hemorrhage, 1 = small amount of hemorrhage (present on no more than 1 brain section), 2 = medium amount of hemorrhage (present on 2-3 sections), 3 = large amount of hemorrhage (present on > 3 sections, but no subarachnoid blood), 4 = severe hemorrhage = same as 3 but brain also has subarachnoid blood.…”
Section: Infarct Size Intracerebral Hemorrhage Scoresmentioning
confidence: 99%
“…Sections were photographed and inspected for gross hemorrhage. Five brain sections were visually inspected for gross hemorrhage and scored by a rater blinded to treatment using methods previously published by our group (Yenari et al, 1997a(Yenari et al, , 1997b(Yenari et al, , 2006. Only cerebral hemorrhages visible to the naked eye were scored: 0, if there was no gross hemorrhage, 1 = small amount of hemorrhage (present on no more than 1 brain section), 2 = medium amount of hemorrhage (present on 2-3 sections), 3 = large amount of hemorrhage (present on > 3 sections, but no subarachnoid blood), 4 = severe hemorrhage = same as 3 but brain also has subarachnoid blood.…”
Section: Infarct Size Intracerebral Hemorrhage Scoresmentioning
confidence: 99%
“…Thrombolysis with recombinant tissue plasminogen activator (rt-PA) is currently the only approved treatment strategy in acute ischemic stroke (The National Institute of Neurological Disorders and Stroke rt-PA Stroke Study Group, 1995). In an embolic stroke model, the combination of perfusion MRI and DW MRI has demonstrated that rt-PA administration within 1 hour after stroke improves perfusion and reduces ischemic tissue damage (Yenari et al, 1997) (Fig. 2A).…”
Section: Magnetic Resonance Imaging In Pharmaceutical Researchmentioning
confidence: 99%
“…2,3 DWI has very high sensitivity for detecting acute cerebral infarction, 4 and PWI can provide a rapid qualitative measure of tissue perfusion, suggesting that DWI and PWI may be suitable techniques to monitor the efficacy of thrombolytic therapy. Although this has been demonstrated in animal models, 5 few data are available on the use of DWI and PWI in patients treated with rtPA, and to the best of our knowledge there are no reports with angiographic correlation. The authors present the case of a patient who was treated with intra-arterial rtPA and who subsequently underwent DWI and PWI.…”
mentioning
confidence: 99%